2021
DOI: 10.1002/ajcp.12533
|View full text |Cite
|
Sign up to set email alerts
|

Examining Support for University‐to‐Police Reporting Policies for Sexual Assault: The Role of Survivors’ Consent

Abstract: In several states, bills have been introduced that require universities to report sexual assaults to law enforcement. Opponents argue that such policies can compel survivors to disclose against their will, stripping survivors of autonomy and harming campus communities. We used a mixed method approach to examine people’s support for reporting policies that do and do not consider survivor consent: compelled police disclosure (requires a report regardless of victim consent) and consented police disclosure (requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…At the same time, the study was cross-sectional in nature so we are unable to evaluate whether public preferences may change over time or are influenced by highly publicized cases or incidents of high-profile sex crimes involving college students. Finally, the study relied on data collected through the MTurk survey platform, an increasingly popular method to test hypotheses about crime control preferences, particularly involving CSA (Holland et al, 2021). Research has demonstrated that MTurk samples do lack diversity (Levay et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the study was cross-sectional in nature so we are unable to evaluate whether public preferences may change over time or are influenced by highly publicized cases or incidents of high-profile sex crimes involving college students. Finally, the study relied on data collected through the MTurk survey platform, an increasingly popular method to test hypotheses about crime control preferences, particularly involving CSA (Holland et al, 2021). Research has demonstrated that MTurk samples do lack diversity (Levay et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To recruit participants we used Amazon Mechanical Turk (or MTurk), a crowdsourcing platform, which has become a tool in the social sciences to collect public opinion data on a variety of criminal justice- and law-related topics including CSA (see, e.g., Holland et al, 2021; Li et al, 2017). The MTurk human intelligence task (HIT) description included the purpose of the research, detailed what the participants would do (e.g., answer questions to an online survey), the requirements to participate (detailed below), and directions on how to receive the incentive.…”
Section: Methodsmentioning
confidence: 99%
“…Given the pervasive implementation of universal MRPs designating all, or nearly all, employees as mandatory reporters (Holland et al, 2018), victim-survivors’ experiences and preferences as well as trauma-informed practices are currently in direct contradiction to the policy approaches used in most U.S. IHEs. Some may argue that MRPs—even against a survivor’s consent—are still necessary because they allow IHEs to address sexual misconduct and protect the campus community (e.g., Holland, Cipriano, Goodman-Williams, & Diede, 2021). Indeed, the most recent Title IX regulations proposed by the OCR compose the most prescriptive and expansive MRP to date, asserting that requiring most employees to report will be “the most effective way to ensure that a recipient’s program or activity is free from sex discrimination” (Nondiscrimination on the Basis of Sex, 2020, p. 41437).…”
Section: Background On Mrpsmentioning
confidence: 99%
“…Our findings contribute to a growing body of evidence that suggest that a different approach to mandated reporting is needed. For instance, survivors prefer more flexible policies that seek to maximize their agency and autonomy and enable their consent in reporting decisions (Holland et al, 2021a;2021b). Thus, policies that are grounded in mandatory supporting, rather than mandatory reporting, would offer a more evidence-based, trauma-informed, and survivorcentered policy approach (Freyd, 2016;Holland et al, 2018b;2021c).…”
Section: Policy Implicationsmentioning
confidence: 99%